Vitreous hemorrhage after tooth extraction in a patient with proliferative diabetic retinopathy. Issue 2 (March 2016) - Masuda, Issei; Kondo, Keisuke; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract: The occurrence of ocular complications in association with dental treatment is rare. In this article, we present a case of vitreous hemorrhage (VH) in a 42-year-old female with proliferative diabetic retinopathy after the extraction of maxillary left first premolar. Valsalva maneuver was suggested to be the cause of VH.